IOT-ENABLED WEB-BASED MONITORING AND CONTROL SYSTEM FOR SOLAR-POWERED RICE FIELD IRRIGATION PUMPS: A SUSTAINABLE SMART AGRICULTURE DESIGN - Ni Made Sri Ariantini; Riforson Wirawan Julianus Gagola; I Gede Para Atmaja (EDUCATIONE, 2026)
Efficient and sustainable irrigation requires an integrated approach to water management, energy supply, and remote supervision. This study aimed to design an Internet of Things (IoT)-based monitoring and control system for a paddy-field irrigation pump using a web platform and a solar photovoltaic power source. A Research and Development approach was applied through literature review, functional requirement analysis, hardware and software architecture design, control-logic development, interface design, and database modelling. The proposed system uses an ESP32 microcontroller, an HC-SR04 ultrasonic sensor for water-level measurement, a PZEM004T module for voltage, current, power, and energy monitoring, a relay-driven pump actuator, a local LCD, and a photovoltaic energy chain consisting of a solar panel, charge controller, battery, and inverter. The resulting design supports real-time monitoring, automatic operation based on minimum and maximum water-level thresholds, manual web-based control, historical data storage, and protection against critically low water levels and excessive pump power. The architecture also separates sensing, processing, communication, actuation, energy, application, and data-management layers, thereby improving maintainability and future scalability. The design provides a coherent basis for a more flexible and environmentally responsible irrigation system; however, field implementation and performance testing are still required to evaluate sensor accuracy, communication stability, energy efficiency, and long-term reliability.